Optimalisasi Model Student Team Achievment Division (STAD) melalui Teknik Peer Tutoring untuk Meningkatkan Hasil Belajar Matematika Terhadap Peserta Didik Kelas 3 Sekolah Dasar - Ijtihad, Faridul; Purbasari, Imaniar; Noorwahyuni, Lisa (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study is a classroom action research conducted to improve mathematics learning outcomes for third-grade elementary school students. It aimed to implement the Student Team Achievement Division (STAD) model combined with the peer tutoring technique. The research subjects were third-grade students at SD Muhammadiyah Birrul Walidain. The main issue identified was the low level of understanding of measurement material, with 95.3% of students not meeting the Minimum Mastery Criteria. The research applied the Kemmis & McTaggart classroom action research model in two cycles. The results showed a significant improvement in students' average scores, rising from 48.8 (pre-cycle) to 80.7 (cycle 2), with a mastery learning increase reaching 66.7%. The combination of STAD and peer tutoring proved effective in enhancing student participation and understanding, particularly when supported by clearly defined tutor roles and motivating appreciation strategies.